Sustainable Development Goal 1 (No Poverty): Current Status and Challenges in Achieving It by 2030 in Nepal (Punyawati Journal, 2026)
This study analyzes Nepal’s progress toward Sustainable Development Goal 1 (No Poverty) and the challenges hindering progress toward achieving it by 2030. Nepal has made significant reductions in monetary poverty over recent decades, yet multidimensional deprivation persists, particularly among Dalit settlements, female-headed households, and ecologically vulnerable regions, which reflect structural, gendered, and intersectional inequalities. Persistent disparities, limited provincial control over development budgets, political instability, underutilized resources, and dependence on remittances exacerbate vulnerabilities, while climate-related shocks, youth unemployment, and global crises further strain poverty reduction efforts. Despite extensive national-level data, research gaps remain in localized, sub-national, and caste disaggregated information, limiting evidence-based policymaking. Employing a qualitative descriptive methodology, this study draws on secondary data from government reports, international agencies, and academic literature to examine poverty trends, multidimensional deprivation, and institutional effectiveness. Findings show steady progress at the national level but highlight gaps between policy targets and outcomes, uneven regional improvements, and vulnerability to economic and environmental shocks. The study concludes that achieving SDG 1 by 2030 requires targeted, context-specific policies, strengthened local governance, climate adaptive interventions, and sustainable livelihood programs. The findings underscore the need for inclusive, resilient, and equitable strategies, improved data systems, and coordinated reforms to address structural and intersectional inequalities, ensuring sustainable poverty eradication across Nepal.